Globalization, Education and Social Justice
XXIII, 193 p.
Keywords: This, the tenth in the 12-volume series Globalization, Comparative Education and Policy Research, presents cutting-edge research on the major global trends in education, social justice and policy research. Accessible, practical and scholarly, it is a sourcebook of ideas for researchers, practitioners and policy makers around the world. The overview it provides will help map out directions in education, and policy research in the transformative educational landscape of the 21st century. The chapters in the book explore the themes of globalization, social justice and education, the pedagogical ethics of teaching social justice, and classroom inequities, relating specifically to the literacy experiences of black adolescent girls. The chapters critically analyze the dominant discourses about decentralization and comparative education and examine the current resurgence of neo-liberal ideological models in education, both newly constructed and re-invented. To ensure as broad a perspective on the issues as possible, the authors employ a raft of diverse paradigms in comparative education research, ranging from critical theory to globalization. Globalization, Education and Social Justice, with contributions from key scholars worldwide, should be required reading for a broad spectrum of users among policy-makers, academics, graduate students, education policy researchers, administrators, and practitioners.